2018
DOI: 10.3390/ijms19010291
|View full text |Cite
|
Sign up to set email alerts
|

Seed Endophyte Microbiome of Crotalaria pumila Unpeeled: Identification of Plant-Beneficial Methylobacteria

Abstract: Metal contaminated soils are increasing worldwide. Metal-tolerant plants growing on metalliferous soils are fascinating genetic and microbial resources. Seeds can vertically transmit endophytic microorganisms that can assist next generations to cope with environmental stresses, through yet poorly understood mechanisms. The aims of this study were to identify the core seed endophyte microbiome of the pioneer metallophyte Crotalaria pumila throughout three generations, and to better understand the plant colonisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 80 publications
(99 reference statements)
2
33
0
Order By: Relevance
“…Strains were tagged with fluorescent proteins as previously described ( Sánchez-López et al, 2018 ) in order to monitor their colonization to the host plant under similar experimental conditions. The labeled strains were inoculated (10 9 cells mL -1 ) to plants with and without addition of pollutants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains were tagged with fluorescent proteins as previously described ( Sánchez-López et al, 2018 ) in order to monitor their colonization to the host plant under similar experimental conditions. The labeled strains were inoculated (10 9 cells mL -1 ) to plants with and without addition of pollutants.…”
Section: Methodsmentioning
confidence: 99%
“…The labeled strains were inoculated (10 9 cells mL -1 ) to plants with and without addition of pollutants. Their colonization efficiency was investigated with a confocal laser microscope Ultra VIEW VoX, PerkinElmer (Zaventem, Belgium) using an excitation wavelength of 561 nm (red) for mCherry, and 405 (Dapi) for plant cell walls while the confocal pictures were analyzed using ImageJ software and Amira 3D visualization software version 6.1.0 (FEI Visualization Sciences Group, Hillsboro, OR, United States) as previously described ( Sánchez-López et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that seed core microbiome is specific for terroir and emergence [ 15 , 16 ]. Seed microbiomes have diverse seed–microbe interactions, and properties, such as being fast-growing, use as bio-fertilizer, antagonistic properties, and ability to cope with environmental stress [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], and are predicted to be an important biological resource for sustainable agriculture [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…authors described that the association must be a very specific and strong plant microbe interaction, considering that the plant exudes specific toxic methylated compounds such as pyrrolizidine alkaloids (Wink and Mohamed, 2003) to select specific and high specialized microbes, in order to prompt the plant development (Sánchez-López et al, 2018). Therefore, the plant"s selection of crucial symbiotic microorganisms is based on the methylotrophic abilities of the Methylobacterium spp., which might detoxify these compounds and use them as a source of nutrients (Sy et al, 2001).…”
Section: Genomic Fingerprinting and Phylogenetic Analysis Of The Ppfmmentioning
confidence: 99%